Penerapan Kurikulum Merdeka Melalui Teori Konstruktivisme Pada Pembelajaran Pendidikan Agama Islam Kelas X Di SMA Negeri 1 Tebing Syahbandar - Puspita, Dhea; Khairun Nizar, Muhammad Alang; Rambe, Mirza Syadat (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This research aims to analyze the application of the Merdeka Curriculum with constructivism theory in the learning of Islamic Religious Education for class X at SMA Negeri 1 Tebing Syahbandar. The Independent Curriculum, which is designed to provide flexibility for teachers and students, is implemented with a constructivist approach that emphasizes the active role of students in constructing their own knowledge. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results of the research show that the implementation of the Independent Curriculum in Islamic Education subjects has gone well, marked by teachers understanding what is done in implementing the independent curriculum and students playing an active role in Islamic Education learning using constructivism theory in the independent curriculum. The teacher plays the role of a facilitator who helps students in the knowledge construction process. Learning evaluation is carried out through three types of assessments, namely diagnostic, formative and summative assessments, which are used to measure student understanding and skills. The conclusion of this research is that the Merdeka Curriculum with a constructivist approach is effective in increasing student involvement, promoting deeper understanding of the material, and building critical, creative and independent character.